(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2020)
Liquid electrodes of domperidone maleate (DOMP) imprinted polymer were synthesis based on precipitation polymerization mechanism. The molecularly imprinted (MIP) and non-imprinted (NIP) polymers were synthesized using DOMP as a template. By methyl methacrylate (MMA) as monomer, N,Nmethylenebisacrylamide (NMAA) and ethylene glycol dimethacrylate (EGDMA) as cross-linkers and benzoyl peroxide (BP) as an initiator. The molecularly imprinted membranes were synthesis using acetophenone (APH), di-butyl sabacate (DBS), Di octylphthalate (DOPH) and triolyl phosphate (TP)as plasticizers in PVC matrix. The slopes and limit of detection of liquid electrodes obtained from the calibration curves ranged from (-18.88– -29.01) mV/decade and (4.0 × 10-5 – 6.0 × 10-5) M, respectively and the response time was about 60 seconds. The Liquid electrodes were filled with (10-2 M) standard solution of the drug and observed stable response for a pH ranged from 2.0 to 11.0 and with good selectivity for over several species. The fresh electrodes of synthesis were effectively used in the pharmaceutical sample to determine DOMP without any time consuming pretreatment measures.